2014
DOI: 10.1007/s00572-014-0558-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical properties influence “black truffle” fructification in plantations

Abstract: Although the important effects of pH and carbonate content of soils on "black truffle" (Tuber melanosporum) production are well known, we poorly understand the influence of soil physical properties. This study focuses on physical soil characteristics that drive successful production of black truffles in plantations. Seventy-eight Quercus ilex ssp. ballota plantations older than 10 years were studied in the province of Teruel (eastern Spain). Soil samples were analyzed for various edaphic characteristics and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Some of the available nutrients and mineral elements, such as the organic matter, effective nitrogen, available phosphorus, available manganese, available calcium and available magnesium, were slightly higher in ectomycorrhizosphere soil during symbiotic stage than CK.S. The differences observed in soil properties may contribute to the synthesis of truffle ectomycorrhizas [30, 5658], since the important effects of soil properties, such as pH and carbonate content, on “black truffle” ( Tuber melanosporum ) production are well known. Compared with the black truffle T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the available nutrients and mineral elements, such as the organic matter, effective nitrogen, available phosphorus, available manganese, available calcium and available magnesium, were slightly higher in ectomycorrhizosphere soil during symbiotic stage than CK.S. The differences observed in soil properties may contribute to the synthesis of truffle ectomycorrhizas [30, 5658], since the important effects of soil properties, such as pH and carbonate content, on “black truffle” ( Tuber melanosporum ) production are well known. Compared with the black truffle T .…”
Section: Discussionmentioning
confidence: 99%
“…Ectomycorrhizal fungi can improve nitrogen and water acquisition of host plants, playing a key role in the nutrition of forest trees [2729]. The colonization of ectomycorrhizal fungi causing higher soil porosities, which has proven to play a crucial role in achieving success in black truffle plantations [30]. Nevertheless, some indirect effects of the truffle ectomycorrhizal symbiosis have not been investigated, such as the effects on other soil microbes, and how the endophytic bacteria of host plants may interact with the mycorrhizal synthesis and affect plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…They also can improve water and nitrogen acquisition of the host plants and play a key role in the nutrition acquisition of forest trees ( Liese et al, 2018 ). The colonization of ECM induces higher soil porosities, which has been proven to play a crucial role in achieving success in black truffle plantations ( Alonso Ponce et al, 2014 ). Our previous studies have shown that the growth of T. indicum alters the microbial communities of ectomycorrhizosphere soil and ectomycorrhizae of P. armandii ( Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A sustainable management of wild mushrooms requires a thorough comprehension of the factors driving mushroom production and temporal variability. Control of mushroom production is related to multiple environmental factors such as site soil characteristics (Barroetaveña et al ., ; Alonso Ponce et al ., ), endogenous dynamics of fungal communities (Smith et al ., ; De Miguel et al ., ), succession (Fernández‐Toirán et al ., ; Baptista et al ., ), forest management (Egli et al ., ; Le Tacon et al ., ), and climate (Baptista et al ., ; Diez et al ., ). Climate is a major component determining mushroom production, particularly during the fruiting period (Boddy et al ., ).…”
Section: Introductionmentioning
confidence: 99%